THE EFFECT OF WORK FLEXIBILITY ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION AS MEDIATION IN A LOGISTICS COMPANY - Junaidi Amrin, Muhammad; Abadi, Ferryal (LPSDI Bina Patria, 2024)
This study was conducted to explore the effect of work flexibility on employee performance with job satisfaction as mediation. This research is expected to contribute positively to the science of organizational management and company management. This study used a survey method with questionnaires as a data collection tool, which was distributed online and offline to mechanical and driver employees of logistics service companies in the city and regency of Tangerang. The study will be conducted in January 2023. The data was processed using the Path Analysis method which used regression 2 times. Respondent selection using purposive sampling method. The results showed that there was a significant relationship between Job Flexibility and employee performance, both directly and through mediating variables of job satisfaction. This can be seen from the correlation coefficient of 0.732 which means that the Independent Variables of Work Flexibility and Job Satisfaction have a strong relationship with the dependent variable of Employee Performance .